Latina Super-heroines: Hot Tamales in Tights vs. Women Warriors, Wrestlers and Guerrilla Fighters of La Raza - Fernández Rodríguez, Carolina (Complutense Journal of English Studies, 2015)
The year 1977 saw the making of the first Latino superhero by a Latino artist. From the 1980s onwards it is also possible to find Latina super-heroines, whose number and complexity has kept increasing ever since. Yet, the representations of spandexed Latinas are still few. For that reason, the goal of this paper is, firstly, to gather a great number of Latina super-heroines and, secondly, to analyze the role that they have played in the history of American literature and art. More specifically, it aims at comparing the spandexed Latinas created by non-Latino/a artists and mainstream comic enterprises with the Latina super-heroines devised by Latino/a artists. The conclusion is that whereas the former tend to conceive heroines within the constraints of the logic of Girl Power, the latter choose to imbue their works with a more daring political content and to align their heroines with the ideologies of Feminism and Postcolonialism.